PPM1H is down-regulated by ATF6 and dephosphorylates p-RPS6KB1 to inhibit progression of hepatocellular carcinoma - Xiaoshuang Yang; Jianting Guo; Wei Li; Chunrui Li; Xilin Zhu; Ying Liu; Xiaopan Wu (Elsevier, 2023)
We have shown previously that polymorphism of activating transcription factor 6 (ATF6) is associated with susceptibility to hepatocellular carcinoma (HCC). Therefore, genes down-regulated by ATF6 might play a tumor-suppressing role. In the present study, we identified that expression of protein phosphatase magnesium- or manganous-dependent 1H (PPM1H) mRNA and protein can be inhibited by ATF6 in hepatoma cells and mice with liver Atf6 knockdown. Tumor tissues from 134 HCC patients were analyzed by immunohistochemistry, and PPM1H exhibited higher expression levels in adjacent para-cancer tissues than in HCC tissues. Therefore, patients with higher expression of PPM1H had a better prognosis. PPM1H inhibited proliferation, migration, and invasion of hepatoma cells. In addition, PPM1H inhibited induced HCC nodule formation as well as tumor xenograft growth in diethylnitrosamine/CCl4-induced HCC mouse model and nude mouse tumorigenicity assay, respectively. A 3D model of PPM1H was obtained by homology multi-template modeling, and ribosomal protein S6 kinase B1 (RPS6KB1) in the bone morphogenetic protein (BMP)/transforming growth factor β (TGF-β) pathway was screened out as the potential substrate of PPM1H by Rosetta. PPM1H could directly dephosphorylate p-RPS6KB1. To conclude, we discovered RPS6KB1 as a new PPM1H dephosphorylation substrate. PPM1H exhibited a suppressive effect on HCC progression by dephosphorylating p-RPS6KB1.